Micro X-ray Fluorescence Study of Late Pre-Hispanic Ceramics from the Western Slopes of the South Central Andes Region in the Arica y Parinacota Region, Chile: A New Methodological Approach. Issue 10 (October 2016) - Flewett, Samuel; Saintenoy, Thibault; Sepúlveda, Marcela; Mosso, Edward Fabian; Robles, Carolina; Vega, Katherine; Gutierrez, Sebastian; Romero, Alvaro; Finney, Lydia; Maxey, Evan; Vogt, Stefan
Archeological ceramic paste material typically consists of a mix of a clay matrix and various millimeter and sub-millimeter sized mineral inclusions. Micro X-ray fluorescence (XRF) is a standard compositional classification tool and in this work we propose and demonstrate an improved fluorescence map processing protocol where the mineral inclusions are automatically separated from the clay matrix to allow independent statistical analysis of the two parts. Application of this protocol allowed us to enhance the discrimination between different ceramic shards compared with the standard procedure of working with only the spatially averaged elemental concentrations. Using the new protocol, we performed an initial compositional classification of a set of 83 ceramic shards from the western slopes of the south central Andean region in the Arica y Parinacota region (Chile). Comparing the classifications obtained using the new versus the old (average concentrations only) protocols, we found that some samples were erroneously classified with the old protocol. From an archaeological perspective, a broad and heterogeneous regional sample set was used in this experimental study due to the fact that this was the first such analysis to be performed on ceramics from this region. This allowed a general overview to be obtained, however further work on more specific sample sets will be necessary to extract concrete archaeological conclusions.